Effect of repeated eccentric demands placed on the lower limb musculature during simulated Rugby Union play - Brown, Lisa Gill (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2010)
Epidemiological studies consistently report that muscular strains are a primary injury type in rugby union with the majority of the strains occurring to the quadricep and hamstring musculature. Recently it has been suggested that poor eccentric muscular strength is a precursor to hamstring and quadriceps strains during intermittent sports that require rapid acceleration and deceleration. Despite the high incidence of these muscle injuries in Rugby Union there has been little research into the possible mechanisms involved. Thus, the purpose of this study was to measure the physiological and perceptual responses during a simulated Rugby Union laboratory protocol and further, to identify changes in muscle recruitment patterns and muscle strength over time by comparing this protocol to a continuous, constant load protocol covering the same distance. The experimental condition (EXP) required university level players to perform 80 minutes of simulated rugby union play in a laboratory setting (on a walkway of 22m) which was compared to that of a control condition (CON) which involved subjects covering the same distance, at a constant speed of 4.2km.h-1 on a treadmill. Physiological, biophysical and perceptual responses were measured pre-, at half-time and post-protocol. Heart rate was significantly (p<0.01) greater as a result of EXP in comparison to the CON. Electromyography (EMG) of the vastus medialis was significantly (p<0.01) greater during the CON protocol. The EXP condition elicited higher iEMG activity in the hamstring musculature at all time intervals. In addition the iEMG of the semitendinosus decreased significantly (p<0.01) as a result of the EXP protocol. Peak eccentric knee extensors (EXT) (-13.19%) and flexors (FLEX) (-12.81%) torque decreased significantly during the experimental protocol. After passive half-time (236.67 + 56.27Nm (EXT) and 173.89 + 33.3NM (FLEX)) and at the end of the protocol (220.39 + 55.16Nm and 162.89 + 30.66Nm) reduced relative to pre protocol (253.89 + 54.54Nm and 186.83 + 33.3Nm). Peak eccentric knee extensors did not change during the control protocol. Central"Ÿ and "ŸLocal" Rating of Perceived Exertion values were significantly (P<0.01) greater during the EXP protocol with an increased incidence of hamstring discomfort and perceived pain (5 out of 10). The EXP protocol resulted in significantly (p<0.01) increased incidence of delayed onset muscle soreness (DOMS). In conclusion, a stop-start laboratory protocol elicited increased heart rate, negatively impacted on muscle activity of the hamstrings, decreased eccentric strength in the lower limb musculature, resulted in increased ratings of Central"Ÿ and Local"Ÿ exertion and increased pain perception and increased incidence of DOMS. Thus, a stop-start rugby specific laboratory protocol has a negative impact on performance. Due to the specificity of the protocol being designed to match the demands of competitive match play it is expected that these changes in heart rate, muscle activity and strength, particularly eccentric strength, will impact negativity on performance during rugby match play and increase the likelihood of injury
Keywords: Sports injuries; Muscles -- Wounds and injuries; Tendons -- Wounds and injuries; Muscles -- Examination; Rugby football injuries; Rugby Union football players